Students’ experiences in learning physical education in an online environment - Diciano, Jovince; Mateo, Wendy; Junior, Romel Juan; Versoza, John Isaiah; Tindowen, Darin Jan (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2021)
The start of the Novel Corona Virus in 2019 has been the root cause of the severe disruption of economic opportunities and educational curriculum implementation affecting people's daily living across the world. In the field of education, the pandemic has brought changes to the educational system. A shift in the mode of learning has shifted from face-to-face to online and modular learning, wherein the former has been utilized more. This basic qualitative study was conducted to explore the experiences of students along with their recommendations to further improve the delivery of online physical education. Twenty informants from the different departments of the University of Saint Louis participated in this study through online interviews. In utilizing open coding, axial coding, and selective coding, the results revealed five major recurring themes, to wit: (1) Student-Teacher Interaction, (2) Technology-Related Experience, (3) Online Classroom Experience, (4) Pedagogical-Related Experience, and (5) Personal-Related Experiences. The study concluded that students have both desirable and undesirable experiences in learning online physical education amidst the COVID-19 Pandemic. The informants’ recommendations focused mainly on the teacher’s regular monitoring of students, the use of effective online strategies in teaching physical education, and providing enough time for activities. In addition, implications and recommendations are also discussed.